A one government approach for agroecology policy coordination in Zimbabwe - Marenya, Paswel P.; Chiduwa, Mazvita S.; Ngoma, Hambulo; Chipindu, Lovemore; Nohayi, Ngowenani; Chimonyo, Vimbayi G.P. (Taylor and Francis, 2025)
In Zimbabwe, as in many other countries, agroecological transitions are often hindered by coordination and execution challenges, rather than by insufficient policy aspirations. Such aspirations, or political intentions, are found in many policy and policy-oriented documents. This study synthesizes 18 government policy documents, academic literature, and an influence-interest mapping exercise to assess the alignment and coordination of agroecology policies in Zimbabwe. Using machine learning-based text analysis, we evaluate thematic congruence across these documents in relation to agroecology principles. The results suggest that the key constraint is not the absence of supportive policies but rather, unclear mechanisms to align and coordinate them effectively. To address these challenges, we propose two approaches: the development of a transcendent agroecology theory of change (in the service of policy coherence) and a "One Government" approach for enhanced inter-sectoral coordination at lower jurisdictions and last-mile implementation. We posit that the analytical framework used here can be applied in real-world policy monitoring, focusing on agroecology or other social objectives.